DEVELOPMENT OF DIGITAL BOOK LEARNING MEDIA FOR MATHEMATICS USING DIGITAL LITERACY-BASED CORPORATE FLIP PDF - Lilis Saputri; Sahat Saragih; Elvis Napitupulu (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
Specifically, it examines (1) the feasibility of using these digital books and (2) their practicality digital books in a real classroom setting. The research follows Plomp's development model, which includes three stages: initial investigation, development or prototyping, and assessment. The study focuses on class X students at SMK Taman Siswa Binjai. To gather data, questionnaires were distributed to media and material experts to evaluate the feasibility of the digital book learning media. Additionally, student response questionnaires were used to assess the practicality of these digital books. The data analysis examined the validity and practicality of the digital book learning media created with Flip PDF Corporate, based on digital literacy. The findings reveal that the developed digital book learning media is highly feasible, with an impressive feasibility score of 98%. Moreover, the practicality assessment showed that students found the digital book products very practical, with a high approval rating of 94.72%. Future research should consider conducting longitudinal studies to evaluate the long-term effects of using digital book learning media on students' knowledge retention, critical thinking skills, and motivation. This research provides valuable insights into the sustainability and effectiveness of digital learning media.